Electron transfer in oriented donor–acceptor dyads, intralayer charge migration, and formation of interlayer charge separated states in multi-layered Langmuir–Schäfer films. Issue 43 (30th October 2020) - Alekseev, Alexander; Efimov, Alexander; Chukharev, Vladimir; Ivanov, Artem; Lemmetyinen, Helge
Abstract : Photo-induced ET efficiencies were determined quantitatively layer-by-layer through multilayered porphyrin–fullerene dyad films. Abstract : Photoinduced intra- and interlayer electron transfer (ET) of doubly bridged donor–acceptor molecule, porphyrin–fullerene dyad (PF), was studied in single- and multi-layered Langmuir–Schäfer (LS) films and in LS films, where PF and an efficient electron donating polymer polyhexyltiophene (PHT) formed a bilayer PHT/PF and multi-layered PHT/PF structures. The ET through layers were investigated by a method, which measures the photovoltaic (PV) response proportional to the number of charge-separated (CS) states and to the CS distance between the electrons and holes formed in pulsed photo-excitation. Primary conclusions were, that ET starts as formations of CS dyads (P + F − ) in single-layers, continues as long-range intra-layer charge migrations following interlayer CS between two adjacent monolayers. Quantitative conclusions were, that the interlayer ET efficiency is 100% in the bi-layered PF structure (2PF), where two CS dyads in adjacent layers forms CS complexes (P + F/PF − ) and that the probability to form longer or higher order of CS complexes follows an expression of a convergent geometric series, with a converting factor of 2/3. In the PHT/PF bilayer structure the ET efficiency was one order of magnitude higher, than that for the 2PF structure due to the ET from the CS dyads to ground state electron donor PHT, with an acceptor density, much higher than that of (P + F − ).